Ética e responsabilidade social empresarial : uma análise a partir de Hans Jonas - Frizzo, Fábio André (My University, 2015)
This research has as a main topic the corporate social responsibility and its relationship to ethic, delimited on the internal dimension of the companies. The principal theoretical reference is the work of the German philosopher Hans Jonas, entitled The Imperative of Responsibility: in search of an ethics for the technological age. The objective is to analyze in what sense the ethic theory of Hans Jonas can contribute to a foundation to the behavior of the internal management of companies, with the purpose is to open the way for his legitimation as a socially responsible organizations for sustainable development. The study starts from the analysis of the conceptual evolution of the term corporate social responsibility, whereby it tries to justify the reason that the company became the object of social responsibility over time and why ethic has become a fundamental element to understand a meaning for the term. The corporate social responsibility is historically artificially required by a contract. But the contract has not been able to regulate effectively the power that emanate from the frenetic advances in science and technology. In this sense, the ethical dimension appears as a hope in trying to put a limitation to the use of that power, under penalty that the humanity will be led to a tragic future. Then, is presented an analytical interpretation of Hans Jonas The Imperative of Responsibility, allowing an understanding of your idea relative to the responsibility and the reason that the author puts it the center of ethic. The responsibility principle is made as an ethical imperative which seeks the technology power in order to avoid the predictable human essential death and humanity physical destruction. It is a responsibility naturally assumed in respect to a supreme end: the preservation of life and the human essence. Before concluding, some assumptions are listed in order the company can be considered socially responsible, among which the economic dimension seen as a middle and not as an end. At the end, is analyzed in what sense the responsibility principle can be interpreted as a reference to the ethical behavior of the internal management of companies for what these ones might assume its real social responsibility from there, with a view to the sustainable development.
Esta pesquisa tem como tema principal a responsabilidade social empresarial e sua relação com a ética, delimitada na dimensão interna das empresas. O principal referencial teórico é a obra do filósofo alemão Hans Jonas, intitulada O princípio responsabilidade: ensaio de uma ética para civilização tecnológica. O objetivo é analisar em que sentido a teoria de Hans Jonas pode contribuir para fundamentar o comportamento da gestão interna de empresas, com o intuito de abrir caminho para a sua legitimação como organizações socialmente responsáveis em prol do desenvolvimento sustentável. O estudo se dá a partir da análise da evolução conceitual do termo responsabilidade social empresarial; através da qual se tenta justificar por que a instituição empresa tornou-se objeto da responsabilidade social ao longo do tempo e por que a ética converteu-se em elemento fundamental à compreensão de um significado para o termo. A responsabilidade social empresarial é historicamente requerida artificialmente por meio de um contrato. Mas o contrato não tem dado conta de regular com eficácia o poder que emana dos avanços frenéticos da ciência e da tecnologia. Nesse sentido, a dimensão ética aparece como uma esperança na tentativa de colocar-se uma limitação ao uso desse poder, sob pena de a humanidade ser conduzida a um futuro trágico. Assim, é apresentada uma interpretação analítica do princípio responsabilidade de Hans Jonas, permitindo uma compreensão da sua ideia em relação ao conceito de responsabilidade e da razão de tê-la colocado no centro da ética. O princípio responsabilidade é formulado como um imperativo ético que visa o controle do poder tecnológico, a fim de evitar as previsíveis morte essencial humana e destruição física da humanidade. Trata-se de uma responsabilidade naturalmente assumida em respeito a um fim supremo: a preservação da vida e da essência humana. Antes de concluir, são elencados alguns pressupostos, para que a instituição empresa possa ser considerada socialmente responsável, dentre os quais, a dimensão econômica, vista como um meio e não como um fim. Ao final, analisa-se em que sentido o princípio responsabilidade pode ser interpretado como um referencial ético ao comportamento da gestão interna das empresas, para que essas possam vir a assumir sua verdadeira responsabilidade social a partir daí, com vistas ao desenvolvimento sustentável.
Keywords: Ética empresarial; Responsabilidade social da empresa; Desenvolvimento sustentável; Business ethics; Social responsibility of business; Sustainable development